PENGARUH PENGGUNAAN MEDIA ARABIC DOMINO TERHADAP HASIL BELAJAR BAHASA ARAB MATERI MUFRODAT SISWA KELAS III DI MI AL-KAUTSAR LAMONGAN - Musa’adatul Fithriyah (AT-THULLAB : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2018)
Mufrodat material is one of the Arabic material that is taught in primary education or Madrasah Ibtidaiyah. In Mufrodat learning media needs to be used to make it easier to convey it and cause motivation to learn to students. In fact the learning of Mufrodat class III material at MI Al-Kautsar Lamongan there is a problem that is student learning outcomes that are less than the Minimum Mastery Criteria (KKM), which is 75 one of the causes of the learning media used is only limited to the use of book media and the use of blackboards. This study aims to determine the effect of the use of Arabic Domino media on learning outcomes of Arabic Mufrodat Material for third grade students of MI Al-Kautsar Lamongan. This study uses a quantitative approach pre-experimental type with one group design pre-test post-test. The data analysis technique used independent t-test with the significance of 0.05. The results of the study are based on the results of the paired sample t-test analysis using the SPSS 15 application with a significance requirement of 0.05 indicating that the value of Sig = 0,000 is smaller than the error rate of 0.05 then Ha is accepted meaning the influence of Arabic Domino media on student learning outcomes. In addition, the results of the analysis of the average value of students before and after using Arabic Domino media obtained a pretest value of 62.95 and a posttest score of 83.25 an increase of 20.3. Based on the analysis of the hypothesis test and analysis of the average value of student learning outcomes as a whole it can be concluded that there is an influence of the use of Arabic Domino media on the learning outcomes of Arabic material Mufrodat grade III students in MI Al-Kautsar Lamongan